AWARENESS LEVEL OF HALAL FOOD PRODUCTS AND HEALTHY LIFESTYLES FOR REALIZING SDGs (COMPARATIVE STUDY BEFORE AND WHEN COVID- 19) - Nadya Salsabila Haqqoni; Fitria Putri Aprilia; Indah Nur Maulina (Universitas Airlangga, 2020)
The emergence of Coronavirus Disease (COVID-19) in China at the end of 2019 has caused a large international outbreak that threatens public health. COVID-19 is a new type of virus that has not been previously identified in humans. This study aims to determine whether this virus affects the public in consuming halal food products and adopting a healthy lifestyle. Islam itself has introduced the terms halal and haram where when this is not prioritized it will cause harm to human health. This study uses descriptive-quantitative methods, with data collection techniques using primary data sourced from a questionnaire with a total of 101 respondents through purposive random sampling technique with the SPSS program and secondary data sourced from literature studies as a theoretical reinforcement in finding a solution that can answer the problem. research written. Our results show that there is an increase in awareness of the halal label and the tendency to consume halal food after the occurrence of COVID-19. In order to realize the SDG's goals, it is necessary to increase public awareness of the halal lifestyle and be strengthened by the results of the survey that has been conducted, we recommend a system that is implemented in 3 ways, namely regulation, education, and literacy (REL). The initiative is intended to maintain and increase public awareness of consuming halal food products so as to accelerate the growth of the halal industry in Indonesia.